STRENGTHENING THE CHARACTER OF ELEMENTARY SCHOOL STUDENTS THROUGH THE SEKAPO PROGRAM BASED ON DEEP LEARNING IN ELEMENTARY SCHOOL - Ikhsan Maulana; Nur Indah Istiqomah; Slamet Widodo; Anam Sutopo; Sutama (Universitas Islam Negeri Mataram, 2025)
This study aims to examine and describe the strengthening of the character of elementary school students through the Sekapo Program, which means